2009
DOI: 10.1177/0734242x09103824
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of households’ willingness-to-pay for private solid waste management services in Ibadan, Nigeria

Abstract: The study examined the determinants of willingness-to-pay for private solid waste disposal systems by urban households in Ibadan, Nigeria. A multistage random sampling technique was used to select 552 households for the study. Data obtained from survey were analysed using a logit model-based contingent valuation. Evidence from the logit model indicated that seven variables had significant influence on the households' willingness-to-pay. Of these, income and asset owned were positive and significant at P < 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 8 publications
6
29
1
Order By: Relevance
“…A reason may be that individuals tend to maximize utility at least cost, hence the higher the price of the service the lower will be the demand for it. Similar result has been reported in other study by Rahji and Oloruntoba (2009). They found that households in Ibadan, Nigeria, were less willing to pay higher prices for improved solid waste services.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…A reason may be that individuals tend to maximize utility at least cost, hence the higher the price of the service the lower will be the demand for it. Similar result has been reported in other study by Rahji and Oloruntoba (2009). They found that households in Ibadan, Nigeria, were less willing to pay higher prices for improved solid waste services.…”
Section: Resultssupporting
confidence: 80%
“…Although in some Nigerian cities such as Lagos and Ibadan residents pay for residential waste management service Rahji and Oloruntoba 2009;Yusuf et al 2007), the waste management service has not been very successful. The residents do not often participate in negotiating prices for waste management service thus the service is either overvalued or undervalued.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, urban residents' valuations regarding private sector participation in municipal solid waste (MSW) management can help policy-makers to package waste management that might be more acceptable and cost efficient, there are only few published studies on contingent valuation regarding waste management in developing countries (e.g. Altaf and Deshazo, 1996;Rahji and Oloruntoba, 2009;Murad et al, 2007). The study reported in this paper will help to fill the knowledge 'gap'.…”
mentioning
confidence: 96%